Implementasi Kompetensi Pedagogik Guru Pendidikan Agama Kristen dalam Meningkatkan Motivasi Belajar Siswa - Hermin Ranting; Lidya Jowangkay (Sekolah Tinggi Agama Kristen Samarinda, 2022)
Abstract: It cannot be denied that it is still found in the field of Christian religious educators regarding pedagogical competence is still lacking in teaching in the classroom. As a result, the learners who are taught do not develop their learning motivation. Those who act as educators do not think about how to overcome so that students grow their learning interest, because it tends to be just an executor of obligations. That is why the underlying topic of this article is outlined by the researcher. In outlining this article, the author applies qualitative methods with a literature study approach accompanied by interviews in obtaining data in this article. The results of the discussion on this topic: (1) pedagogical competence that should be owned by a teacher in cultivating student learning interest is, (a) able to manage learning, including: planning, implementation, assessment. (b) Able to develop learning strategies, (c) able to develop themselves sustainably, through increasing knowledge and work professionals, (d) able to reflect on work results, (e) able to increase student learning motivation until students achieve the level of mastery as expected. The efforts that need to be made to improve student learning motivation are (a) making changes in classroom organizing, the use of learning methods, teaching and learning strategies, (b) acting as facilitators, (c) creating effective learning conditions by actively engaging students. This is in line with how Jesus taught His strengtheners, the pedagogical element was implemented in his ministryAbstrak: Tidak bisa dipungkiri bahwa masih ditemukan dilapangan adanya tenaga pendidik agama Kristen mengenai kompetensi pedagogiknya masih kurang dalam mengajar di kelas. Imbasnya, nara-didik yang diajar tidak berkembang motivasi belajarnya. Mereka yang berperan sebagai pendidik pun tidak memikirkan bagaimana mengatasi agar nara-didik tumbuh minat belajarnya, karena cenderung hanya pelaksana kewajiban. Itulah sebabnya yang mendasari topik artikel ini diuraikan oleh peneliti. Di dalam menguraikan artikel ini, penulis menerapkan metode kualitatif dengan pendekatan studi literatur disertai wawancara dalam memperoleh data pada tulisan ini. Hasil pembahasan pada topik ini: (1) komptensi pedagogik yang sepatutnya dimiliki oleh seorang guru dalam menumbuhkan minat belajar siswa adalah, (a) mampu mengelola pembelajaran, meliputi: perencanaan, pelaksanaan, penilaian. (b) Mampu mengembangkan strategi pembelajaran, (c) mampu mengembangkan diri secara berkelanjutan, melalui meningkatkan pengetahuan dan professional kerja, (d) mampu melakukan refleksi hasil kerja, (e) mampu meningkatkan motivasi belajar siswa hingga siswa mencapai taraf penguasaan sesuai yang diharapkan. (2) Upaya-upaya yang perlu dilakukan untuk meningkatkan motivasi belajar siswa adalah (a) melakukan perubahan dalam pengorganisasian kelas, penggunaan metode belajar, strategi belajar mengajar, (b) bertindak sebagai fasilitator, (c) menciptakan kondisi belajar yang efektif dengan melibatkan siswa secara aktif. Ini sejalan bagaimana Yesus ketika mengajar para pengkut-Nya, unsur pedagogik itu terimplementasikan dalam pelayanannya.